PsycEXTRA Dataset 1998
DOI: 10.1037/e422462008-001
|View full text |Cite
|
Sign up to set email alerts
|

Entry into the criminal justice system: A survey of police arrests and their outcomes: Home Office research study 185

Abstract: The Home Office Research Studies are reports on research undertaken by or on behalf of the Home Office. They cover the range of subjects for which the Home Secre t a ry has re s p o n s i b i l i t y. Titles in the series are listed at the b a ck of this re p o rt (copies are ava i l able from the address on the back c over).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(113 citation statements)
references
References 14 publications
6
105
2
Order By: Relevance
“…• Eyewitness identifications were found by Phillips and Brown [17] to play a role in around 90% of arrests made at ten police stations across England and Wales (and was the main source of evidence relied upon in sexual offences and offences involving the use of violence against the person the eyewitness testimony of the victim).…”
Section: The Pertinence Of Cognitive Bias To the Forensic And Investimentioning
confidence: 99%
“…• Eyewitness identifications were found by Phillips and Brown [17] to play a role in around 90% of arrests made at ten police stations across England and Wales (and was the main source of evidence relied upon in sexual offences and offences involving the use of violence against the person the eyewitness testimony of the victim).…”
Section: The Pertinence Of Cognitive Bias To the Forensic And Investimentioning
confidence: 99%
“…Unfortunately, while appropriate adults often provide important welfare protections for children and young people, a downside for the young detainee can be having to wait for them to attend at the police station. In one study, for example, while half of the appropriate adults appeared within one hour, 21% took two or more hours to attend (Phillips and Brown, 1998). 18 More recently, Pierpoint (2008) noted that appropriate adult services provided by voluntary schemes seemed to be quicker than parents or professional services.…”
Section: The Role Of Appropriate Adultsmentioning
confidence: 99%
“…For example, Phillips' and Brown's (1998) study of 1993/4 custody records found that juveniles requested advice at a lower rate than adults (33% compared to 39%). However, they suggested that the lower take-up of legal advice was due to juveniles being dealt with for less serious offences than adults.…”
Section: Marks the 25mentioning
confidence: 99%
“…Considerable research has centred upon the implementation and efficacy of Code C of the 1984 Police and Criminal Evidence Act (Bean & Nemitz, 1994;Bradley, 2009;Brown, Ellis, & Larcombe, 1992;Bucke & Brown, 1997;Gudjonsson et al, 1993;Irving & McKenzie, 1989;Medford, Gudjonsson, & Pearse, 2003;NAAN, 2015;Palmer & Hart, 1996;Phillips & Brown, 1998). The Codes of Practice document the role and use of an "Appropriate Adult" (AA) to support the welfare and legal rights of the detained mentally disordered/vulnerable detainee (Code C: Home Office, 2014).…”
Section: Police and Mental Illnessmentioning
confidence: 99%